1994
DOI: 10.1109/70.313095
|View full text |Cite
|
Sign up to set email alerts
|

Control of rolling contacts in multi-arm manipulation

Abstract: When multiple arms are used to manipulate a large object, it is beneficial and sometimes necessary to maintain and control contacts between the object and the effector (the contacting surface of an arm) through force closure. Rolling and/or sliding can occur at these contacts, and the system is characterized by holonomic as well as nonholonomic (including unilateral) constraints. In this paper, the control of planar rolling contacts is investigated. Multi-arm manipulation systems are typically redundant. In ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

1996
1996
2003
2003

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(45 citation statements)
references
References 36 publications
0
44
0
1
Order By: Relevance
“…Once the backbone curve is determined for an assumed location of the end-effector, depending on the physical implementation morphology of a particular manipulator, various fitting algorithms can be developed. This method has been utilized to form the foundation for obstacle avoidance [10], locomotion [11], and motion control [12], [13]. Some researchers have shown the application of the modal ap- The authors are with the Department of Mechanical Engineering, Villanova University, Villanova, PA 19085 USA (e-mail: farbod.fahimi@villanova.edu; hashem.ashrafiuon@villanova.edu; c.nataraj@villanova.edu).…”
Section: An Improved Inverse Kinematic and Velocity Solution For Spatmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the backbone curve is determined for an assumed location of the end-effector, depending on the physical implementation morphology of a particular manipulator, various fitting algorithms can be developed. This method has been utilized to form the foundation for obstacle avoidance [10], locomotion [11], and motion control [12], [13]. Some researchers have shown the application of the modal ap- The authors are with the Department of Mechanical Engineering, Villanova University, Villanova, PA 19085 USA (e-mail: farbod.fahimi@villanova.edu; hashem.ashrafiuon@villanova.edu; c.nataraj@villanova.edu).…”
Section: An Improved Inverse Kinematic and Velocity Solution For Spatmentioning
confidence: 99%
“…When two or three robots are tightly coupled together in a specified formation for a specified manipulation task, the control problem is well-defined and the feedback control laws for coordinating a small team of robots are reasonably well understood [11]- [13]. The feedback laws for coordinated control of manipulation and locomotion are discussed by [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure rolling motion, by definition, the tangential components of the relative linear velocities between the arms and the object at each contact point must be zero, that is (25) (26) (27) (28) Additionally, if the component of the relative angular velocity along the contact normal is zero, we achieve what is called pure rolling. If we impose this no-spin condition on the relative angular velocity we get (29) (30) Equations (25)- (30) are nonholonomic constraints.…”
Section: B Constraint Analysismentioning
confidence: 99%
“…The difference between the results of [6], [15] and this paper is that we are able to control the trajectory of contact points as well as the position/orientation of the object. Paljug et al [25], [24] demonstrated the control of rolling and contact forces in multiarm manipulation for two dimensional objects. But since rolling in two dimensions introduces only holonomic constraints, the problem was much simpler.…”
Section: Previous Workmentioning
confidence: 99%
“…Paljug et al (1994) investigated the problem of multi-arm manipulation. Erdmann (1998a) showed how to manipulate a known object with two palms.…”
Section: Nonprehensile Manipulationmentioning
confidence: 99%